2018
DOI: 10.1007/s11547-018-0932-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial chemoembolization combined with simultaneous DynaCT-guided radiofrequency ablation in the treatment of solitary large hepatocellular carcinoma

Abstract: DynaCT-guided TACE + RFA is safe and feasible for the treatment of solitary large HCCS. TACE combined with simultaneous RFA provides a new treatment option for solitary large HCCs in which DynaCT has important clinical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Following TACE, we now use DynaCT to scan the tumor and reconstruct 3D images for the puncture site and the route planning [28]. Wang needle can accurately penetrate the target lesions of 46 patients and achieve favorable clinical results [29]. Therefore, DSA system with DynaCT allows for simultaneous combination of TACE and MWA in one intervention operation and more accurate puncture for ablation needles.…”
Section: Discussionmentioning
confidence: 99%
“…Following TACE, we now use DynaCT to scan the tumor and reconstruct 3D images for the puncture site and the route planning [28]. Wang needle can accurately penetrate the target lesions of 46 patients and achieve favorable clinical results [29]. Therefore, DSA system with DynaCT allows for simultaneous combination of TACE and MWA in one intervention operation and more accurate puncture for ablation needles.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that sorafenib combined with TACE followed by RFA 3 ± 2 days later is a feasible and effective method in the treatment of large HCCs complicated by types I/II PVTT. Although several studies on this approach have been performed (26,27), the optimal timing of this combined therapy remains unclear. The majority of clinicians recommend that RFA should be performed 1 week to 1 month after TACE (26); however, in this study, cTACE and RFA were performed sequentially (separated by 3 ± 2 days).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of clinicians recommend that RFA should be performed 1 week to 1 month after TACE (26); however, in this study, cTACE and RFA were performed sequentially (separated by 3 ± 2 days). An advantage of this nearconcurrent treatment with TACE and RFA is the avoidance of lipiodol and chemotherapeutic clearance, which would possibly allow for the formation of new collateral vessels and vascular recanalization (27). TACE effectively inhibited the nutrient vessel supply to the tumor, and it alleviated the effectiveness of blood circulation on heat ablation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] With the development of cone-beam CT and angio-CT, a single-session combination of TACE and RFA has become a new and effective choice for the treatment of solitary large HCCs with satisfactory outcomes. [10][11][12][13] In solitary large HCCs, as in many other cancers, identifying potential predictors of locoregional therapy response remains important.…”
Section: Introductionmentioning
confidence: 99%